Hybrid switched‐capacitor‐based boost DC–DC converter with reduced voltage stress - Tan Luong Van; Thanh Hai Nguyen (The Journal of Engineering, 2024)
Abstract This article presents the new hybrid switched‐capacitor (SC)‐based transformerless DC–DC converter with a high step‐up capability and common ground features. The proposed hybrid SC‐based converter provides low voltage stress across semiconductor devices to utilize MOSFETs with lower Rdson and low voltage ratings. In addition, the diodes in SC cells with low voltage stress can reduce the reverse recovery power loss of the converter. Thus, the overall efficiency of the proposed hybrid SC‐based converter can be increased. The converter circuit, operating principle, and design guidelines of the proposed hybrid SC‐based converter are discussed. To confirm the performance of the proposed hybrid SC‐based converter, a detailed comparison study with the conventional hybrid SC converter is also presented. Finally, a laboratory prototype with 200 W and 25 to 200 V is set up to verify the effectiveness of the proposed hybrid SC‐based converter.